2022
DOI: 10.3934/dcdss.2021161
|View full text |Cite
|
Sign up to set email alerts
|

A novel bond stress-slip model for 3-D printed concretes

Abstract: <p style='text-indent:20px;'>This paper considers the 3D printing process as a discontinuous control system and gives a simple and coherent bond stress-slip model for a new and intelligent building 3-D printed concrete. The previous models focused on either the maximal stress or the maximal slip, however, the novel model uses an energy approach by the dimension analysis, so that the main factors affecting the bond stress-slip relationship can be clearly revealed, mainly including the concrete's propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The idempotent of the multiplicative semigroup of higher tropical matrices has been a hot topic in mathematics, and the multiple-noise removal is to harness the tropical algebra's basic properties. Due to its inherent filtering property, the tropical algebra will open up a totally new window for noise removal, some advanced applications include 3-D printing technology [41][42][43] and machine learning. 44 Tropical addition can replace traditional addition as a more effective filter in denoising.…”
Section: Applicationsmentioning
confidence: 99%
“…The idempotent of the multiplicative semigroup of higher tropical matrices has been a hot topic in mathematics, and the multiple-noise removal is to harness the tropical algebra's basic properties. Due to its inherent filtering property, the tropical algebra will open up a totally new window for noise removal, some advanced applications include 3-D printing technology [41][42][43] and machine learning. 44 Tropical addition can replace traditional addition as a more effective filter in denoising.…”
Section: Applicationsmentioning
confidence: 99%
“…In this paper, the two-scale fractal theory [26][27][28] is adopted to establish a fractal-fractional differential model for the graphene N/MEMS. The two-scale fractal is now widely used for fractal vibration systems, [29][30][31][32][33] the fractal diffusion, 34,35 porous concretes, [36][37][38] and dynamic economics. 39 Nonlinear problems are relatively complex, and it is difficult for us to obtain an exact solution of a nonlinear equation.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the two-scale fractal theory 2628 is adopted to establish a fractal-fractional differential model for the graphene N/MEMS. The two-scale fractal is now widely used for fractal vibration systems, 2933 the fractal diffusion, 34,35 porous concretes, 3638 and dynamic economics. 39…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies have revealed that the graphene distribution in a composite affected its properties greatly ( Zuo and Liu, 2021 ; Zuo, 2021 ). Geometry is always the main factor affecting materials’ properties ( He, et al, 2021b ) so that the energy absorption property of the polar bear hair.…”
Section: Introductionmentioning
confidence: 99%